Case 3743: Allodaposuchus precedens Nopcsa, 1928 (Crocodyliformes: Eusuchia: Allodaposuchidae): proposed designation of a neotype - Narváez, Iván; Brochu, Christopher A; Celis, Ane de; Delfino, Massimo; Escaso, Fernando; Pérez-García, Adán; Rabi, Márton; Ortega, Francisco (Bulletin of Zoological Nomenclature, 2017)
The purpose of this application, under Article 75.5 of the Code, is to set aside all type fixations for the crocodyliform Allodaposuchus precedens Nopcsa, 1928, and to designate a neotype. The type series of A. precedens includes specimens from the Maastrichtian (Late Cretaceous) of Vălioara, housed at the Magyar Állami Földtani Intézet (Hungarian Geological Institute) in Budapest, Hungary. The original material includes several cranial and postcranial elements thought to correspond to the same specimen but the attribution of this set of remains as belonging to one individual cannot be confirmed. Therefore, subsequent papers considered only part of this set, a fragmentary skull table, as the lectotype of A.precedens. Given the recent description of several species closely related to A. precedens and the lack of a combination of exclusive characters that can diagnose the species based on the specimens studied by Nopcsa, we request that the Commission set aside all previous type fixations and designate a neotype for A. precedens. The neotype designation is of utmost importance for the objective identification of this species, which is necessary for future phylogenetic analyses and assessments of crocodyliform diversity.
Keywords: Allodaposuchidae; Allodaposuchus; Allodaposuchus precedens; Eusuchia; neotype; Nomenclature; taxonomy; Upper Cretaceous